2022
DOI: 10.1097/dcr.0000000000002380
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Redo Ileocolonic Resection for Crohn’s Disease: A Preliminary Report From a Tertiary Care Center

Abstract: BACKGROUND: Although the safety of laparoscopic redo ileocolonic resection for Crohn’s disease has been described before, the safety of robotic redo ileocolonic resection is still unelucidated. OBJECTIVE: This study aimed to share our preliminary experience regarding the safety of robotic redo ileocolonic resection for Crohn’s disease. DESIGN: Retrospective analysis. SETTING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Robotic procedures were successfully performed in those cases, without an increase conversion rate. These results are similar from those reported by Mayo clinic, which showed no statistically signi cant difference regarding the overall length of hospital stay, the 30-day morbidity, 30-day mortality or anastomotic leaks occurred in recurrent vs non recurrent group (19). Furthermore, 30.5% of our patients had intra-abdominal stula and/or required multivisceral resections and repair.…”
Section: Discussionsupporting
confidence: 91%
“…Robotic procedures were successfully performed in those cases, without an increase conversion rate. These results are similar from those reported by Mayo clinic, which showed no statistically signi cant difference regarding the overall length of hospital stay, the 30-day morbidity, 30-day mortality or anastomotic leaks occurred in recurrent vs non recurrent group (19). Furthermore, 30.5% of our patients had intra-abdominal stula and/or required multivisceral resections and repair.…”
Section: Discussionsupporting
confidence: 91%
“…Abd El Aziz et al investigated robotic redo ileocolic resection versus primary robotic resection. 27 A study found that compared to primary resection, redo resection had no difference in length of stay or 30-day morbidity. The only difference was in the rate of conversion to open (16.7% redo vs. 2.5% primary).…”
Section: Minimally Invasive Technique In Recurrent Diseasementioning
confidence: 99%
“…The use of robotic platforms in colorectal surgery has grown exponentially over the last years 5,6 . A few reports from referral centres showed that robotic surgery is also feasible in the treatment of IBD and is associated with comparable or even improved postoperative outcomes as compared to the laparoscopic approach [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%